The Effect of Compensation on Employee Performance Through Work Discipline as an Intervening Variable at Panahmas Dwitama Distrindo Ltd. Jember - Vika Dhelia Pristiawati; Rahmat Agus Santoso (Publikasi Indonesia, 2021)
Panahmas Dwitama Distrindo Jember is a product distributor company of Unilever Indonesia Ltd. has low employee discipline and decreased productivity of employee performance is one of the problems this company faces. This study aims to see the effect of compensation on employee performance through work discipline as an intervening variable at Panahmas Dwitama Distrindo Ltd. Jember. This research method uses quantitative research methods by taking 60 respondents. Answer the problem formulation with the help of Smart Partial Least Square (PLS) 3 and analyze the data using the Partial Least Square (PLS) analysis technique. The study results show that compensation has a negative and insignificant effect on employee performance, compensation has a positive and significant effect on work discipline. Work discipline has a positive and significant effect on employee performance, and compensation has a positive and significant effect on performance. Employees through work discipline as an intervening variable.